Pemilihan Excavator Kelas 50 Ton untuk Usaha Pertambangan Sirtu Galian C Melalui Penerapan Metode Analytical Hierarchy Process (AHP)) - Irawan, Dany; Achmadi, Fuad (Jurnal Bisnis dan Keuangan, 2017)
The selection process of excavator in mine workings of sand & gravel mine type C is one of important process, because in this process, mining industrialist wants an exact and suitable investment with necessary with applying the method and appropriate criteria. The enterprise hope can get the good profit with appropriate method in Excavator selection. The problem of this research is the plan of enterprise for add the capacity of production with buy the excavator 50 ton class as the main loading equipment 20 ton class, so need the study for measure the criteria in selection of excavator. The aim of this research is for help the company for having the appropriate take system and be able to use for the company in investment selection and make more easier to find out the most optimal aspect between the aspects in decision of excavator selection. The method that used as the analysis tool in this study is using AHP (analytical hierarchy process) method with using the comparing of criteria that fixed. From the result of the analysis and alternative decision of excavator about multi attribute, the first position is K excavator (34,4%), the second position is C excavator (33,4%), and the last position is D excavator (32,2%)